2018
DOI: 10.1111/bjc.12198
|View full text |Cite
|
Sign up to set email alerts
|

Brief group‐based acceptance and commitment therapy for stroke survivors

Abstract: Acceptance and commitment therapy (ACT), delivered didactically to groups of stroke survivors, proved feasible and acceptable. ACT had benefits, relative to treatment as usual, for depression, health status, and hope. Several secondary outcome variables did not show dependable benefit for ACT: anxiety; health-related quality of life; and mental well-being. Results should be treated as preliminary as the sample size was small, blinding was not possible, concomitant treatments were not monitored, and there was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 76 publications
(92 reference statements)
2
62
0
1
Order By: Relevance
“…Positive expectancies such as general self-efficacy and hope are associated with greater psychological flexibility as well as less experiential avoidance and anxiety sensitivity (Ciarrochi, Sahdra, Marshall, Parker, & Horwath, 2014;Ruiz, 2014;Wicksell et al, 2012). A number of studies indicate that hope and general self-efficacy increase among populations with illnesses who have completed ACT (Ghasemi, Dehghan, Farnia, Tatari, & Alikhani, 2016;Majumdar & Morris, 2019;Wicksell et al, 2012). In addition, greater selfefficacy for coping by effectively regulating emotions is associated with acceptance of negative emotions and less emotion suppression (Kivity, Tamir, & Huppert, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Positive expectancies such as general self-efficacy and hope are associated with greater psychological flexibility as well as less experiential avoidance and anxiety sensitivity (Ciarrochi, Sahdra, Marshall, Parker, & Horwath, 2014;Ruiz, 2014;Wicksell et al, 2012). A number of studies indicate that hope and general self-efficacy increase among populations with illnesses who have completed ACT (Ghasemi, Dehghan, Farnia, Tatari, & Alikhani, 2016;Majumdar & Morris, 2019;Wicksell et al, 2012). In addition, greater selfefficacy for coping by effectively regulating emotions is associated with acceptance of negative emotions and less emotion suppression (Kivity, Tamir, & Huppert, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, novel psychological interventions are emerging that may be worthy of consideration. For example, acceptance and commitment therapy (Majumdar & Morris, 2019) is a psychological intervention that focuses on promoting acceptance and pursuit of a valued life, whilst acknowledging physical limitations and psychological distress. Positive psychology based interventions (Cullen et al, 2018) may enhance wellbeing by increasing experiences of pleasure, engagement and meaning by focusing on character strengths such as gratitude, optimism, hope and personal growth.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no large RCTs have been conducted investigating the effectiveness of ACT for anxiety and depressive symptoms following TBI or stroke. However, earlier studies have shown promising results [29–31]. The aim of the proposed study is to investigate the clinical and cost effectiveness of an upcoming cognitive behavioural therapy, ACT, for anxiety and depressive symptoms following ABI.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is some evidence that people who developed depressive or anxiety symptoms after ABI can benefit from ACT. Majumdar and Morris [29] performed a randomized controlled trial (RCT) in which an ACT group-intervention of four weekly didactic PowerPoint sessions was compared to treatment as usual in stroke survivors. They found that people in the ACT intervention showed a significant reduction in depression and increased hopefulness and self-rated health.…”
Section: Introductionmentioning
confidence: 99%